Aktualisasi Nilai Adiwiyata Pada Konstelasi Pembelajaran di Sekolah - Nadila Putri Megananda; Suyitno; Desy Anindya (Pengembangan Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
The Adiwiyata program is an award given by the government as recognition or appreciation to educational institutions that fully implement environmentally focused education. This study aims to provide an explanation of how in class IV of UPT SD Negeri Kanigoro 03, the Adiwiyata program is used. The qualitative case study conducted interviews with teachers and students, classroom observation, and analysis of documents related to the adiwiyata program to collect data. The results showed that using adiwiyata learning at UPT SDN Kanigoro 03 improved learning outcomes. Students not only acquire academic knowledge, but they also learn the principles of sustainability, preservation of the school environment, and social responsibility. As a result, it can improve students' understanding of their surrounding environment and their learning outcomes.